Customer Relationship Management (CRM) Analysis and Design to Provide Customer Service in The Culinary Field (Case Study Restaurant XYZ) - Sfenrianto, Lorio Purnomo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There has been a lot of discussion regarding Customer Relationship Management (CRM) in recent years, where the CRM function to provide customer service in the culinary field has been widely applied by culinary business entrepreneurs. Restaurant XYZ, which started the culinary business in 2018, will design a CRM system to improve service to its customers, this is because it has not been optimal in the process of providing services to its customers. Before doing the design, an analysis phase is needed which is carried out using the Fishbone Method, this method is expected to help in analyzing the constraints and needs of the Restaurant XYZ in the best CRM design. The design using the Diagram Unified Modeling Language (UML) and User Centered Design (UCD) approach, is expected to create a CRM system as expected by the owner of Restaurant XYZ. The CRM that has been planned is expected to help the owner in providing services to Restaurant XYZ customers.